2019
DOI: 10.3389/fmicb.2019.00659
|View full text |Cite
|
Sign up to set email alerts
|

The Majority of Active Rhodobacteraceae in Marine Sediments Belong to Uncultured Genera: A Molecular Approach to Link Their Distribution to Environmental Conditions

Abstract: General studies on benthic microbial communities focus on fundamental biogeochemical processes or the most abundant constituents. Thereby, minor fractions such as the Rhodobacteraceae are frequently neglected. Even though this family belongs to the most widely distributed bacteria in the marine environment, their proportion on benthic microbial communities is usually within or below the single digit range. Thus, knowledge on these community members is limited, even though their absolute … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
51
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 80 publications
(53 citation statements)
references
References 101 publications
1
51
1
Order By: Relevance
“…Several studies have observed the proliferation of copiotrophic taxa longitudinally during SSW, including genera within the families Flavobacteriaceae , Rhodobacteriacaea ( Lloyd and Pespeni, 2018 ), Actinobacteria, and genera in the orders Altermonadales ( Nuñez-Pons et al, 2018 ), Vibrionales and Oceanospiralles ( Hoj et al, 2018 ). These taxonomic groups are amongst the most active constituents of bacterioplankton and major players in marine OM degradation, some of which have facultative anaerobic metabolisms ( Pinhassi et al, 2004 ; Choi et al, 2010 ; Buchan et al, 2014 ; Thiele et al, 2017 ; Pohlner et al, 2019 ). While it is tempting to ascribe pathogenicity traits to groups that are enriched on disease-affected tissues (based on members of the same family or genus causing pathology), or infer their role in community dysbiosis (i.e., the microbial boundary effect), this is not possible in the absence of demonstrated pathogenicity or strain-level assignment ( Hewson, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have observed the proliferation of copiotrophic taxa longitudinally during SSW, including genera within the families Flavobacteriaceae , Rhodobacteriacaea ( Lloyd and Pespeni, 2018 ), Actinobacteria, and genera in the orders Altermonadales ( Nuñez-Pons et al, 2018 ), Vibrionales and Oceanospiralles ( Hoj et al, 2018 ). These taxonomic groups are amongst the most active constituents of bacterioplankton and major players in marine OM degradation, some of which have facultative anaerobic metabolisms ( Pinhassi et al, 2004 ; Choi et al, 2010 ; Buchan et al, 2014 ; Thiele et al, 2017 ; Pohlner et al, 2019 ). While it is tempting to ascribe pathogenicity traits to groups that are enriched on disease-affected tissues (based on members of the same family or genus causing pathology), or infer their role in community dysbiosis (i.e., the microbial boundary effect), this is not possible in the absence of demonstrated pathogenicity or strain-level assignment ( Hewson, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…Draconibacterium (phylum Bacteroidetes) is another genus that contains marine sediment-derived bacteria, providing merit to the detection of this bacterium when water was shallowest (Du et al 2014, Gwak et al 2015. The Rhodobacteraceae (Alphaproteobacteria) are some of the most widely spread bacteria in the ocean and a study analyzing distribution and classification of Rhodobacteraceae found that onethird of the detected Rhodobacteraceae correlated to sediment parameters, indicating there are specific sediment-associated Rhodobacteraceae (Pohlner et al 2019). Rhodobacteraceae strains have been isolated from mangrove sediments (Yu et al 2018, Ren et al 2019.…”
Section: Discussionmentioning
confidence: 99%
“…(Hoj et al, 2018). These taxonomic groups are amongst the most active constituents of bacterioplankton and major players in marine OM degradation, some of which have facultative anaerobic metabolisms (Pinhassi et al, 2004;Choi et al, 2010;Buchan et al, 2014;Thiele et al, 2017;Pohlner et al, 2019). While it is tempting to ascribe pathogenicity traits to groups that are enriched on disease-affected tissues (based on members of the same family or genus causing pathology), or infer their role in community dysbiosis (i.e.…”
Section: Shifts In Heterotrophic Bacterial and Archaeal Communities Dmentioning
confidence: 99%